Influence of Anthocyanins, Derivative Pigments and Other Catechol and Pyrogallol-Type Phenolics on Breast Cancer Cell Proliferation - Iva Fernandes (2010)
Anthocyanins (cyanidin-3-glucoside (Cy-3-gluc) and delphinidin-3-glucoside (Dp-3-gluc)) and their respective vinylpyranoanthocyanin-catechins (portisins) were studied in order to evaluate the cytotoxicity effect on the estrogen responsive human breast cancer cell line (ER+) MCF-7 and their effect on estrogen receptor (ER-alpha and ER-beta) expression. Other flavonoid classes and phenolic molecules were also tested, aiming to study possible structural features related with these effects. Also, the anti-proliferative effect of Cy-3-gluc and Dp-3-gluc was studied by an immunofluorescence assay. Generally, all the anthocyanin pigments studied inhibited, in a dose-dependent manner, the growth of the (ER+) MCF-7. The cytotoxicity effect was higher when cells were treated with Dp-3-gluc and its respective portisin. Altogether, the results point to the ortho trihydroxylated moiety in the phenolic ring as an important structural feature for more potent cytotoxicity effect oil MCF-7 cells comparatively to the effect observed with the similar dihydroxylated compounds. In order to elucidate the molecular mechanism involved, expression of estrogen receptor was assayed by RT-PCR and real time RTPCR. The higher antiproliferative effect observed after cell treatment with Dp-3-gluc was not followed by modification on ER expression. However, the anthocyanin Cy-3-gluc was able to induce a downregulation of ER levels although with no significant effect on MCF-7 proliferation.